(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Today, one of the most pressing problems in the world community is radicalism and extremism. However, in scientific discourse there is a pluralistic approach to these phenomena. The absence of unique and generally accepted definitions of terms in practice has certain difficulties in assessing these phenomena, determining the level of potential hazards and creating the necessary countermeasures. For this reason, the article analyzes the most widespread phenomena of public life from the point of view of radicalism and extremism. In addition, each term has its own characteristics and the reasons for their existence in society. The main goal of the article is to define the concept of radicalism by studying the work of Western, Russian and domestic researchers and distinguishing them from the notion of extremism. To achieve this goal, the history of the term radicalism was examined, the features of the history of development in Great Britain and Germany were analyzed. Particular attention was paid to the etymological basis of the term “radicalism” and its significance in each historical period. In the future, the results of the research can be used to prepare programs to counter religious extremism and terrorism, information groups for clichés, as well as to prepare lectures on such subjects as religious studies, history, political science and sociology of religion. Key words: radicalism, radical, extremism, terrorism, term.